Health : Indigenous Knowledge, Equitable Benefits - Moran, Katy (World Bank, Washington, DC, 2012)
The note looks at the intellectual property rights connected with the use, and value of medicinal plants, which has become a metaphor to describe indigenous ownership of traditional knowledge, generating options for contractual mechanisms to ensure benefits return to source cultures, and countries. However, through time, the extinction rate of species, and cultures continues to accelerate, while human health further deteriorates from diseases for which no cure exists. The note seeks answers on how to apply lessons from the Convention on Biological Diversity, and how to move on to implementing such lessons. Through the case study in Nigeria, practical information shows how countries, companies, and cultures can cooperate. It explains the work of the Bio-Resources Development and Conservation Program, organized as a focal point for collaborative research, that builds technical skills in Nigeria, thus generating pharmaceutical leads that target therapeutic categories for tropical diseases. Within this setting, Sharman Pharmaceuticals established a research relationship with scientific institutions, village communities, and traditional healers, which uses the science of ethno-botany, and that of natural product chemistry, medicine and pharmacology, to create an efficient drug discovery process. Recommendations on remaining issues, and future progress are presented.